EXPORT OF AGRICULTURAL PRODUCTS TO EU COUNTRIES: STATUS AND PROSPECTS - Гирич, Сергій; Василишина, Ольга (SWorldJournal, 2024)
The article analyzes the state and prospects of agricultural exports to the EU. It is noted that Russia's full-scale invasion has caused significant damage to Ukraine's economy and, as a result, has significantly reduced budget revenues, which significant